Al-Attas's Works and Contributions to the Islamic Architecture in Malaysia - Ali, Aizan; Ladjal, Tarek; Hamid, Faisal Abdul; Fauzi, Nurulwahidah; Grine, Fadila (IDOSI, 2013)
Several studies have been conducted on al-Attas' educational philosophy and other field of knowledge such as traditional Islam, religion and spirituality, but not on his contributions to the Islamic Architecture in Malaysia. This article examines Al-Attas's contributions to the Islamic Architecture. This study involves applied deductive, inductive and comparative analyses for the most apparent architectural elements which comprise of the Malay, Roman, Greek and Moorish design. He was given a task by Ministry of Education, Malaysia to contextualize the Islamic education and implement it at higher educational level, leading towards the concept and design of International Institute of Islamic Thought and Civilization (ISTAC). This study implies that the Islamic architectural concept of the building exhibits his skill and artistic talent with a solid blend of his knowledge and experience. Further studies are required on his contribution to Sufism that influences his architectural concept. ©IDOSI Publications, 2013.